PENGARUH KARAKTERISTIK PENGAWASAN DEWAN KOMISARIS TERHADAP AGRESIVITAS PAJAK PERUSAHAAN - Akbar Bintang Pradana; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
This study aims to analyze the influence of the board of commissioners against corporate tax aggressiveness. Characteristics of the board of commissioner's oversight affecting tough tax aggressiveness. The characteristics of the board of commissioner's oversight affecting tax aggressiveness are presented by the effectiveness of the internal control system, type of external auditor, the size of the audit committee, and the frequency of meetings of the board of commissioners. This research refers to research conducted by Richardson et al (2013). This study uses secondary data obtained from the financial statements of manufacturing companies listed on the stock exchanges of Indonesia in 2012-2015. This study used as many as 188 samples with purposive sampling method. Data analysis with the classical model of multiple regression. The results obtained from this research is the effectiveness of internal control system and the frequency of meetings of the board of commissioners has no effect on corporate tax aggressiveness. The type of external auditor and the size of the audit committee influenced the corporate tax aggressiveness.